Athletes` ease of imaging predicts their imagery and observational learning use - Williams, S. E.; Cumming, J. (Psychology of Sport and Exercise, 2012)
Objectives: Following the development of the Sport Imagery Ability Questionnaire (SIAQ; Williams & Cumming, 2011), the aim of the present two studies was to more comprehensively examine the relationship between sport-related imagery ability and the functions of imagery and observational learning (OL) athletes report. A second aim was to establish the SIAQ`s predictive validity.